The rise and fall of the Soviet Empire - Crozier, Brian 1918-2012 (Forum, 1999)
"Brian Crozier tells the brutal history of the Soviet Empire - its birth, life, and sudden death. The book begins at the beginning, in 1917, when the oversized dreams of Lenin and the happenstance of events conspired to change the course of history. Crozier follows the Soviet conquests across Europe and into Asia, Africa, and the Western Hemisphere. He uses recently declassified information from Soviet archives to add texture and depth to the story - the betrayal at Yalta, the terror of Stalin, the tragedy of Hungary, the split with China, the false hope of Prague Spring, the rise of Castro, the invasion of Afghanistan, and the crumbling of the Berlin Wall. Revealed along the way is the dark underside of a regime whose march toward supremacy resulted in the loss of tens of millions of lives."